INDICATIVE DEPENDENCE OF TIREDNESS OF ALUMINUM ALLOY CRYSTALLITES - Карускевич, М. В.; Радченко, О. І.; Корчук, О. Ю. (Proceedings of National Aviation University (archive), 2021)
The results of testing samples of aluminum alloy with a special coarse-grained structure, which allowed to determine the crystallographic orientation by X-ray diffraction analysis, are considered. The relationship between the crack propagation velocity and the crystallographic orientation is established. The correlation equations of fatigue fracture kinetics are obtained.